Adiponectin Deficiency Triggers Bone Loss by Up-Regulation of Osteoclastogenesis and Down-Regulation of Osteoblastogenesis - Yang, Jihyun; Park, Ok-Jin; Kim, Jiseon; Han, Sora; Yang, Young; Yun, Cheol-Heui; Han, Seung Hyun (Frontiers in Endocrinology, 2019)
Osteoporosis and bone disorders related to the metabolic syndrome are often associated with adipokines secreted by adipocytes in bone. Adiponectin, a type of adipokine, is a regulator of immune responses and metabolic processes, but its role in bone biology remains uncertain. We investigated the role of adiponectin in bone metabolism using adiponectin-deficient mice in vivo and in vitro. Adiponectin-deficient mice exhibited reduced bone mass and increased adiposity. Adiponectin-deficient calvarial cells were prone to differentiate into adipocytes rather than osteoblasts. Although macrophages from adiponectin-deficient mice had low osteoclastogenic potential as osteoclast precursors with increasing interferon regulatory factor 5 expression, under co-culture conditions with calvarial cells and bone marrow derived macrophages, the enhanced receptor activator of nuclear factor κB ligand/osteoprotegerin (RANKL/OPG) ratio of adiponectin-deficient mesenchymal progenitor cells facilitated osteoclast differentiation. In addition, increased RANKL/OPG ratio was observed in the bone marrow extracellular fluid of adiponectin-deficient mice compared to that of wild-type mice. Notably, recombinant adiponectin treatment enhanced RANKL-induced osteoclast differentiation from macrophages but up-regulated OPG production in recombinant adiponectin-exposed calvarial cells, which inhibited osteoclast differentiation. Taken together, these results suggest that adiponectin plays an inhibitory role in bone metabolism through cross talk between precursor cells of both osteoclasts and osteoblasts by regulating RANKL/OPG ratio in the bone marrow microenvironment.